Preliminary study on the diagnostic value of urine cell glucose metabolism detection for male urothelial carcinoma - Yaoyao Wu; Angchao Ye; Zhenguo Bu; Shaoxing Zhu; He Wang; Yipeng Xu (Journal of Men's Health)
This study assessed the potential of urine abnormal glycolytic metabolism detection versus urine cytology in diagnosing male urothelial carcinoma, using pathological results as the gold standard. Urine samples were collected from suspected urothelial carcinoma male patients at Zhejiang Cancer Hospital from September 2021 to February 2024. Both urine cell glycometabolism detection and urine cytology examination were performed on the same samples, with clinical data including tumor classification and grading gathered for statistical analysis. A total of 105 male patients were enrolled, with 83 (79.05%) diagnosed with urothelial carcinoma. Stratified analysis based on urine glycometabolism detection (high risk, low risk, no abnormalities) showed the sensitivity, specificity and Area Under Curve (AUC) values of “Glucose metabolism 1” (high risk) as 74.70%, 59.09% and 0.6689 (p = 0.0151), and “Glucose metabolism 2” (high/low risk) as 82.56%, 59.09% and 0.7082 (p = 0.0027). Urine cytology results showed the sensitivity, specificity, and AUC values of “Urine Exfoliative 1” (malignant tumor cells found) as 22.89%, 90.91% and 0.5690 (p = 0.3211), “Urine Exfoliative 2” (finding or suspecting malignant tumor cells) as 42.17%, 90.91% and 0.6654 (p = 0.0174), and “Urine Exfoliative 3” (finding/suspecting/not excluding malignant tumor cells) as 60.24%, 72.73% and 0.6648 (p = 0.0178). The combined diagnosis of “Glucose metabolism 2” and “Urine Exfoliative 4” (no tumor cells found) improved diagnostic efficiency, with sensitivity 62.65%, specificity 95.45% and AUC = 0.7905 (p < 0.0001). “Glucose metabolism 2” had a sensitivity of 86.21% for low-grade urothelial carcinoma, while “Urine Exfoliative 4” had a sensitivity of 58.62%. Compared to urine cytology, urine cell glycometabolism detection improved sensitivity for diagnosing urothelial carcinoma but had lower specificity. Combined diagnosis enhanced sensitivity and specificity, and glycometabolism detection showed superior sensitivity for low-grade urothelial carcinoma, serving as an efficient non-invasive diagnostic tool.